Measuring In-Plane Micro-Motion of Micro-Structure Using Optical Flow - 金翠云 靳世久 栗大超 王建林 (Transactions of Tianjin University, 2009)
Optical flow method is one of the most important methods of analyzing motion images. Optical flow field is used to analyze characteristics of motion objects. According to motion features of micro-electronic mechanical system （MEMS） micro-structure, the optical algorithm based on label field and neighborhood optimization is presented to analyze the in-plane micro-motion of micro-structure. Firstly, high speed motion states for each frequency segment of micro-structure in cyclic motion are frozen based on stroboscopic principle. Thus a series of dynamic images of micro-structure are obtained. Secondly, the presented optical algorithm is used to analyze the image sequences, and can obtain reliable and precise optical field and reduce computing time. As micro-resonator of testing object, the phase-amplitude curve of micro-structure is derived. Experimental results indicate that the measurement precision of the presented algorithm is high, and measurement repeatability reaches 40 nm under the same experiment condition.